F.F. Bosworth the Man behind "Christ the Healer" - Barnes, Roscoe, 1961- (Newcastle upon Tyne : Cambridge Scholars Pub., 2009)
When the Pentecostal movement exploded in 1906 in Zion City, Ill., Fred Francis Bosworth was present. When the Assemblies of God was being formed, Bosworth served as one of its leaders. He also was present as a mentor to the tent revivalists in the 1940s and 1950s. This book is about the life and ministry of Bosworth (1877-1958), a Pentecostal pioneer, musician, famous healing evangelist, and the author of Christ the Healer. He reportedly led over a million people to Christ, and was consider...
Includes bibliographical references (p. [121]-129).
Description based on print version record.
Keywords: Bosworth, F. F. -- 1877-1958.; Evangelists -- United States -- Biography; Spiritual healing -- Christianity; RELIGION / Christian Ministry / Evangelism; Electronic books